Inventarisasi Kerusakan Jalan SDN 04 Damon Bengkalis Dengan Metode PCI Menggunakan ArcGIS 10.8 - Saputra, Yogi Andri; Saputra, Hendra (Jurnal TeKLA, 2024)
This study applies the Pavement Condition Index (PCI) method integrated with ArcGIS 10.8 for Road Damage Data Inventory in SDN 04 Damon, Bengkalis District. This research aims to identify and analyze road conditions around the school, with a focus on road segments that receive a "poor" score according to the PCI. Damage data is obtained through field surveys, then analyzed using the PCI method and ArcGIS spatial visualization. The results reveal that several road segments are classified as "poor," potentially affecting student mobility and safety. The integration of PCI and ArcGIS provides essential information for making accurate road maintenance decisions. This study highlights the importance of road maintenance around educational environments while showcasing the potential of geospatial technology in infrastructure assessment and maintenance. The implications of these findings support the efforts of schools and local governments to improve road conditions and ensure student safety.